Causes of warm‐edge range limits: systematic review, proximate factors and implications for climate change. (29th November 2013) - Cahill, Abigail E.; Aiello‐Lammens, Matthew E.; Caitlin Fisher‐Reid, M.; Hua, Xia; Karanewsky, Caitlin J.; Ryu, Hae Yeong; Sbeglia, Gena C.; Spagnolo, Fabrizio; Waldron, John B.; Wiens, John J.; Daniel Kissling, W.
Abstract Aim The factors that set species range limits underlie many patterns in ecology, evolution, biogeography and conservation. These factors have been the subject of several reviews, but there has been no systematic review of the causes of warm‐edge limits (low elevations and latitudes). Understanding these causes is urgent, given that the factors that set these limits might also drive extinction at warm edges as global climate changes. Many authors have suggested that warm‐edge limits are set by biotic factors (particularly competition) whereas others have stressed abiotic factors (particularly temperature). We synthesize the known causes of species' warm‐edge range limits, with emphasis on the underlying mechanisms (proximate causes). Location Global. Methods We systematically searched the literature for studies testing the causes of warm‐edge range limits. Results We found 125 studies that address the causes of warm‐edge limits, from a search including > 4000 studies. Among the species in these studies, abiotic factors are supported more often than biotic factors in setting species range limits at warm edges, in contrast to the widely held view that biotic factors are more important. Studies that test both types of factors support abiotic factors significantly more frequently. In addition, only 23 studies (61 species) identified proximate causes of these limits, and these overwhelmingly support physiological tolerances to abiotic factors (primarily temperature). Only eight species with identified proximate causes were tested for both biotic and abiotic factors, but the majority support abiotic factors. Main conclusions Although it is often assumed that warm‐edge limits are set by biotic factors, our review shows that abiotic factors are supported more often among the species in these 125 studies. However, few studies both identify proximate causes and test alternative mechanisms, or examine the interaction between biotic and abiotic factors. Filling these gaps should be a high priority as warm‐edge populations are increasingly driven to extinction by climate change.